STRATEGY MANAGEMENT OF INSTAGRAM @SUROBOYOBUS TO INCREASE AWARENESS OF PUBLIC TRANSPORTATION IN SURABAYA CITY SOCIETY - Nabila, Rahmania; Sukardani, Puspita Sari (The Commercium, 2022)
With the presence of social media now, it gave birth to a low budget high impact marketing concept. Instagram is in demand by agencies or companies as a medium to increase engagement in achieving brand awareness in their market target. This study aims to determine the strategy of managing instagram @suroboyobus social media in increasing brand awareness, especially in the people of Surabaya City. For this reason, this research uses a qualitative descriptive approach with a case study method. The method of collecting data by interviewing 4 informants consisting of UPTD PTU staff who are the managers of Suroboyo Buses, e-Dishub staff who act as admins or managers of @suroboyobus instagram accounts, and instagram followers who are also as a Suroboyo Bus passengers. Based on the results of interviews, documentation, and observations, the management strategy of nstagram @suroboyobus use the communication model The Circular Model of SoMe initiated by Regina Lutrell. This model is divided into four parts, namely: Share, Optimize, Manage, and Engage. Strategies in increasing public transportation awareness through the selection of more informative content are considered to be able to increase the engagement of followers and other Instagram users.Keywords : Management Instagram, Suroboyo Bus, Brand Awareness